Alcohol in early Java: its social and cultural significance - Jákl, Jiří (Brill's Southeast Asian library, 2021)
"In Alcohol in Early Java: Its Social and Cultural Significance, Jiří Jákl offers an account of the production, trade, and consumption of alcohol in Java before 1500 CE, and discusses a whole array of meanings the Javanese have ascribed to its use. Though alcohol is extremely controversial in contemporary Islamic Java, it had multiple, often surprising, uses in the pre-Islamic society"--